2008
DOI: 10.1063/1.2896795
|View full text |Cite
|
Sign up to set email alerts
|

Topology Optimization with Stress Constraints: Reduction of Stress Concentration in Functionally Graded Structures

Abstract: Abstract. This presentation describes a topology optimization framework to design the material distribution of functionally graded structures with a tailored Von Mises stress field. The problem of interest consists in obtaining smooth continuous material fraction distribution that produces an admissible stress field. This work explores the topology optimization method for minimizing volume fraction of one of the phases considering stress constraints. Existence of inherent material microstructure requires consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The selection of the grading factors should be preceded by a proper sensitivity analysis or based on studies available in the literature. [57][58][59] For example, Tharun et al, 59 after performing a multi-objective optimization of an FGRD for minimization of stress, deflection and mass, concluded that temperature is a less significant factor in such analysis than the angular velocity.…”
Section: Comments On Optimal Solutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The selection of the grading factors should be preceded by a proper sensitivity analysis or based on studies available in the literature. [57][58][59] For example, Tharun et al, 59 after performing a multi-objective optimization of an FGRD for minimization of stress, deflection and mass, concluded that temperature is a less significant factor in such analysis than the angular velocity.…”
Section: Comments On Optimal Solutionsmentioning
confidence: 99%
“…The selection of the grading factors should be preceded by a proper sensitivity analysis or based on studies available in the literature. 5759…”
Section: Grading Factor Optimizationmentioning
confidence: 99%